Keterampilan Berpikir Tingkat Tinggi dan Hasil Belajar Kognitif Siswa melalui Pembelajaran Kooperatif Berbasis Inkuiri - Ita Ita (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The process of teaching and learning cannot be separated from the efforts to increase the quality of human resources. A good learning process is determined by a good planning which is also pays attention to the environment of the students. After that, the process of learning, evaluation, and observation can be done well. In other words, if those sequences of planning and teaching are implemented well, the process of learning can be said as succesful and it acquires the standards. One part of planning is to prepare the learning process kit. This research is aimed to measure the indicator achievement of high order thinking skill and student’s cognitive study results through cooperative learning based on inquiry using the kit that has been developed. The result of the research using the developed kit through the learning process of XI IPA 1 student’s high order thinking skill indicates two categories of variation, that are good category by 24 students and 2 students are categorised as good enough in thingking skill. This means that on the whole, the high level of students’ thinking skill achieves good result. While students’ cognitive study result during the process of learning has achieved the standard score of minimum score criterion.